Chemosensitizing effect of honokiol in oral carcinoma stem cells via regulation of IL‐6/Stat3 signaling. Issue 11 (4th August 2018) - Chang, Min‐Te; Lee, Shiao‐Pieng; Fang, Chih‐Yuan; Hsieh, Pei‐Ling; Liao, Yi‐Wen; Lu, Ming‐Yi; Tsai, Lo‐Lin; Yu, Cheng‐Chia; Liu, Chia‐Ming
Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common cancers worldwide with poor prognosis. Numerous studies have attempted to explore alternative regimens aimed at reducing cancer stem cells (CSCs) without compromising the efficacy of conventional chemoradiotherapy. The present study sought to assess the effect of a natural compound honokiol on the reduction of elevated cancer stemness, metastatic capacity, and chemoresistance of oral carcinoma stem cells (OCSCs). Our results demonstrated that honokiol attenuated the cell survival and self‐renewal of OCSCs in a dose‐dependent manner. Moreover, honokiol downregulated the expression of 2 selective markers of OCSCs, ALDH1, and CD44, as well as the migration and invasion abilities, indicating its potential to suppress cancer stemness. We showed that honokiol reduced the secretion of IL‐6 and phosphorylation of STAT3, and the honokiol‐inhibited self‐renewal, invasion and colony formation were reversed by administration of IL‐6. Most importantly, our data demonstrated that honokiol was able to potentiate the effect of Cisplatin, leading to a lower proportion of OCSCs and the decreased cancer stemness features. Taken together, this study demonstrated the benefits of utilizing honokiol as an adjunct therapy for OSCC treatment.